Cognitive computing recipes : artificial intelligence solutions using Microsoft cognitive services and Tensorflow /: artificial intelligence solutions using Microsoft cognitive services and Tensorflow. ([2019]) - Masood, Adnan; Hashmi, Adnan
No abstract available